Infección experimental de aves con Campylobacter coli y C. jejuni - Joaquim, Patricia Estefania; Balbiani, Facundo; Socas, Maria Laura; Moreno, Claudia Elvira; Delgado, Fernando Oscar; Chacana, Pablo (Asociación Latinoamericana de Avicultura, 2024)
Poster